Study on pathological factors affecting the sensitivity of neoadjuvant therapy in hypopharyngeal cancer - Gaofei Yin; Nuan Li; Xiaohong Chen; Yang Zhang; Zhigang Huang; Wei Guo (Cancer Immunology, Immunotherapy)
Abstract Objective Hypopharyngeal squamous cell carcinoma (HSCC) is a highly malignant tumor type in the head and neck region. In recent years, neoadjuvant therapy has significantly improved the laryngeal preservation rate among patients. However, there are variations in the efficacy of neoadjuvant therapy, and the identification of reliable predictive biomarkers for its efficacy remains a challenging research focus. This study aims to explore the correlation between the expression of P53, P16, and Ki67 and the response to neoadjuvant therapy. Methods A retrospective analysis was conducted on 120 patients who underwent neoadjuvant therapy at Beijing Tongren Hospital, Capital Medical University, from January 2021 to June 2024. Patients were grouped based on their treatment response and the type of neoadjuvant therapy received. Group analysis were employed to assess the predictive value of P53, P16, and Ki67 for treatment efficacy across different neoadjuvant therapy groups. Results A total of 120 patients were included in the study, with 60 patients each in the good response and poor response groups. The study comprised three neoadjuvant therapy groups: neoadjuvant chemotherapy, neoadjuvant targeted therapy combined with chemotherapy, and neoadjuvant immunotherapy combined with chemotherapy. Each group had 20 patients with good and poor responses, respectively. Among patients with P53 positivity, the effective rate after neoadjuvant therapy was 35.94%, significantly lower than the 66.07% observed in P53negative patients (p = 0.0017). For P16 positivity, the effective rate was 28.57%, lower than the 52.83% in P16negative patients (p = 0.0880). For patients with Ki67 < 60%, the effective rate was 33.33%, significantly lower than the 66.67% in those with Ki67 ≥ 60% (p = 0.0005). Comprehensively evaluate confirmed that P53 positivity and Ki67 < 60% were associated with poor response to neoadjuvant therapy, while P53 negativity and Ki67 ≥ 60% were associated with good response. Conclusion Our findings suggest that the combination of P53 and P16 can be used as a preliminary tool to assess the efficacy of neoadjuvant therapy in patients with HSCC. Specifically, patients with P53 positivity and Ki67 < 60% tend to have lower sensitivity to neoadjuvant therapy. Further research may be needed to clarify the precise role of P16 in HSCC.